The Justifications for Creating a Simple Joint Stock Company as a Special Form for Start-ups - Bouras, Azzeddine; Boukharouba, Hamza (Journal of Legal Studies and Researches, 2024)
The legislator introduced the simple joint stock company pursuant to Law No 22-09 amending and supplementing Order No 75-59 contains the commercial law as a special form for start-ups, this is due to the special nature of this company that is appropriate to the nature of start-ups, in contrast to the traditional forms of commercial companies, which have some inappropriate characteristics due to the nature of these institutions.